2013
DOI: 10.1371/journal.pone.0071044
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-Regulatory Function of Indoleamine 2,3 Dioxygenase through Modulation of Innate Immune Responses

Abstract: Successful long-term treatment of type-1 diabetes mainly relies on replacement of β-cells via islet transplantation. Donor shortage is one of the main obstacles preventing transplantation from becoming the treatment of choice. Although animal organs could be an alternative source for transplantation, common immunosuppressive treatments demonstrate low efficacy in preventing xenorejection. Immunoprotective effects of indoleamine 2,3-dioxygenase (IDO) on T-cell mediated allorejection has been extensively studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 45 publications
4
27
0
Order By: Relevance
“…However, under a similar experimental condition, the number of macrophages was not significantly changed between treated and untreated wounds. This finding is consistent with our previous report indicating that Kyn has no influence on proliferation of macrophages in an in vivo model …”
Section: Discussionsupporting
confidence: 94%
“…However, under a similar experimental condition, the number of macrophages was not significantly changed between treated and untreated wounds. This finding is consistent with our previous report indicating that Kyn has no influence on proliferation of macrophages in an in vivo model …”
Section: Discussionsupporting
confidence: 94%
“…NO is an important macrophage immune effector molecule that is involved in immune regulation and the defense response, and its production is regulated by iNOS (23). When stimulated, Raw264.7 cells produce abundant quantities of NO, which assists macrophages in the immune response against pathogens (20). The results of the present study demonstrate that SAP-1 increased the levels of iNOS gene expression in RAW264.7 cells, and increased the production of NO by RAW264.7 cells.…”
Section: Discussionsupporting
confidence: 57%
“…The sample was centrifuged at 5,000 x g (-4˚C) for 10 min, and the supernatant discarded. The residue was washed with 75% ethanol, and the total RNA was eluted with diethyl pyrocarbonate water (18)(19)(20)(21). The purity of RNA was determined from the A260/A280 ratio using ultraviolet spectrophotometry (Nanodrop ND1000; Thermo Fisher Scientific, Inc.).…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…For example, IDO1 expression has been identified as a determinant of macrophage M1 rather than M2 phenotype, with the enzyme signalling in favour of the anti-inflammatory M2 phenotype [255,256]. Studies in the RAW264.7 murine macrophage cell line indicated that incubation of these cells with IDO1-expressing fibroblasts resulted in reduced NOS2 expression and macrophage viability due to L-Trp deprivation [257]. IDO1-expressing fibroblasts similarly reduced macrophage numbers and xenograft survival in a macrophage-dependent pancreatic islet xenograft-rejection model [257].…”
Section: Lymphocytesmentioning
confidence: 99%
“…Studies in the RAW264.7 murine macrophage cell line indicated that incubation of these cells with IDO1-expressing fibroblasts resulted in reduced NOS2 expression and macrophage viability due to L-Trp deprivation [257]. IDO1-expressing fibroblasts similarly reduced macrophage numbers and xenograft survival in a macrophage-dependent pancreatic islet xenograft-rejection model [257]. Further evidence for control of macrophages by IDO1-expressing bystander cells comes from a report with IDO1-expressing endometrial stromal cells impairing macrophage phagocytic activity in a manner dependent on IL-33 production [258].…”
Section: Lymphocytesmentioning
confidence: 99%